Core–shell nanocarriers for cancer therapy. Part I: biologically oriented design rules. (February 2014) - d'Angelo, Ivana; Conte, Claudia; Miro, Agnese; Quaglia, Fabiana; Ungaro, Francesca
<x xml:space="preserve">Abstract</x> Introduction: The application of nanotechnologies to the cancer field for therapeutic, imaging or diagnostic purposes represents an advanced and very attractive approach to overcome the main limits related to conventional chemotherapy. In particular, core–shell nanocarriers can be engineered to provide adequate features to overcome the main biological barriers encountered by free anti-cancer drugs. Areas covered: This review will try to summarise the design rules – as dictated by biological requirements – to take into account for proper nanocarrier design and to highlight the potential of administration routes other than intravenous. Expert opinion: Although intravenous injection remains the most investigated route of administration for 'nanoncologicals', research interest towards less explored administration routes allowing localised chemotherapy or delivery in close proximity to the tumour site might change the way cancer is treated in the near future. Nevertheless, an experimental set-up more biologically oriented taking into account an in-depth evaluation of stability in complex media, protein interaction, and cell interaction of novel nanoconstructs could allow their successful translation in pre-clinical and clinical settings.